Prevalence of Sexual Dysfunction in Ankylosing Spondylitis and Its Correlation with Disease Activity - Piyush Jain; Avdesh Giri (Journal of Clinical Rheumatology and Immunology)
Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease primarily affecting the spine and pelvis. While studies have extensively explored the physical manifestations of AS, the prevalence of sexual dysfunction in male patients and its association with disease activity remains under-explored. The study aims to determine the prevalence of sexual dysfunction in AS and its association with the disease activity. Methods: This comparative cross-sectional observational study was conducted with sexually active male patients diagnosed with AS. Disease activity was quantified using the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the Ankylosing Spondylitis Disease Activity Score-C-reactive protein (ASDAS-CRP). Functional limitations and the extent of spinal and pelvic involvement were assessed through the Bath Ankylosing Spondylitis Functional Index (BASFI) and the Bath Ankylosing Spondylitis Metrology Index (BASMI), respectively. Sexual function was evaluated using the International Index of Erectile Function-15 (IIEF-15), and psychological status was measured via the Hospital Anxiety and Depression Scale (HADS). Results: The study reveals a significantly higher prevalence of sexual dysfunction among male patients with AS compared to control subjects, with p-values of < 0.0001 across all five domains of IIEF-15 (Fig.1). Notably, domains such as erectile function, orgasmic function, and overall sexual satisfaction were markedly impaired and exhibited a strong negative correlation with increased disease activity, as measured by BASDAI and the ASDAS-CRP. The erectile function scores demonstrated a pronounced negative correlation with disease activity indices, with correlation coefficients of -0.9840 for BASDAI and -0.9669 for ASDAS-CRP (Fig.2). Conclusion: AS is associated with a high prevalence of sexual dysfunction and correlates with disease severity. The results underscore the importance of integrating sexual health assessments into routine clinical evaluations of AS patients and addressing sexual dysfunction as a critical component of comprehensive disease management.